NcRNA-Mediated High Expression of HMMR as a Prognostic Biomarker Correlated With Cell Proliferation and Cell Migration in Lung Adenocarcinoma - Jiang, Xiulin; Tang, Lin; Yuan, Yixiao; Wang, Juan; Zhang, Dahang; Qian, Kebao; Cho, William C.; Duan, Lincan (Frontiers in Oncology, 2022)
Abstract Background: Hyaluronan mediated motility receptor (HMMR) plays a pivotal role in the cell growth. However, the function and potential mechanism of HMMR in lung adenocarcinoma (LUAD) remain unclear. Methods: HMMR expression at the diverse public databases was analyzed, the prognosis of HMMR was analyzed in Gene Expression Profiling Interactive Analysis (GEPIA) database. The gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were analyzed by DAVID and gene set enrichment analysis (GSEA) software. The correlation between HMMR expression and immune cell infiltration was analyzed in Tumor Immune Estimation Resource (TIMER) database, the gene and protein networks were examine by GeneMANIA and STRING databases, The expression of HMMR in LUAD and cell lines were performed by immunohistochemistry (IHC) and qPCR assays, the function of HMMR on cell proliferation and migration were examined by cell growth curve, colony formation, transwell and wound healing assay. Results: In this study, we found that HMMR was elevated in LUAD and its high expression was associated with the poor clinicopathologic features and adverse outcomes in LUAD. Furthermore, our results demonstrated that HMMR expression positively correlate with immune cell infiltration, immune modulator, HMMR expression and diverse immune cell infiltration affect the prognosis of LUAD. Finally, with functional study, depletion of HMMR significantly represses the cell growth and migration of LUAD. Mechanically, we found that DNA methylation/TMPO-AS1/let-7b-5p axis mediated high expression of HMMR in LUAD, depletion of TMPO-AS1 and over-expression the let-7b-5p could result in decreased expression of HMMR in LUAD cells, we found that the TMPO-AS1 was positively correlated with HMMR and negatively correlated with let-7b-5p expression in LUAD. Conclusions: Our findings elucidated that DNA methylation/TMPO-AS1/let-7b-5p axis mediated high expression of HMMR which can serve as a biomarker to predict the prognosis and immune infiltration in LUAD. Keywords: Hyaluronan mediated motility receptor, non-small cell lung cancer, non-coding RNA, immune infiltration